Analisis Penggunaan Teknologi Sistem Informasi Akuntansi (SIA) terhadap Pengendalian Internal - Natasya Saffa Adesti; Suci Alya Rahmadhani; Adi S Kurniawan; Masayu Vrisaliani; Raja Fitriana; Mutia Putri Dewi Apriyanti (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The rapid advancement of information technology has significantly influenced Accounting Information Systems (AIS) playing a crucial role in enhancing the effectiveness and efficiency of internal control within organizations. This study aims to analyze the impact of technology utilization in AIS on internal control. The Research employs a Systematic Literature Review (SLR) method, examining relevant literature on accounting information systems, information technology, and internal control mechanisms. The findings indicate that integrating technology into AIS improve accurancy and timeliness of financial recording and reporting, therby strengthening internal control effectiveness. However chaklengs persist in AIS implementation, including limited user understanding, a shortage of skilled human resources, and insufficient training. These factors can hinder the optimal use of AIS and reduce its impact on internal control. To address these challengs, organization must enhance internal control policies, integrate information technology more effectively, and provide continuous training for employes. These meansure will enable organization to maximize the benefits of AIS in improving financial data accurancy, decision making processes, and overall corporate governance. This study highlights the importance of proper technology adoption and user competency in leveraging AIS for internal control enhancement